2023
DOI: 10.1021/acsmaterialslett.3c00861
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Active Titanium Sulfonate Framework for Photocatalytic Organic Synthesis

Dong-Fei Lu,
Shangda Li,
Ming-Xue Guan
et al.

Abstract: In this work, the first visible-light-active titanium sulfonate metal−organic framework (denoted as FIR-138) with 2-fold interpenetrated srs topology was synthesized by employing 2,5-dihydroxy-1,4-benzenedisulfonic acid (H 4 DOBSC) as ligands. The strong chelating coordination ability of the hydroxyl and sulfonate O atoms from H 4 DOBSC endows the framework of FIR-138 with good stability, while the formation of the Ti-phenolic motif ensures excellent visible light absorption with a bandgap (E g ) of 1.74 eV. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…The excellent and reversible photochromic properties of Cd-MOF- 1 inspired us to investigate its application in ink-free erasable printing. Unlike some reported cases of ink-free erasable printing using filter paper as a substrate, we attempted to mix Cd-MOF- 1 with polydimethicone (PDMS) to prepare an ink-free erasable printing Cd-MOF- 1 @PDMS film. The printing process is shown in Figure a. The template is covered on the film to control the incident area of light so as to realize the printing of the target pattern.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent and reversible photochromic properties of Cd-MOF- 1 inspired us to investigate its application in ink-free erasable printing. Unlike some reported cases of ink-free erasable printing using filter paper as a substrate, we attempted to mix Cd-MOF- 1 with polydimethicone (PDMS) to prepare an ink-free erasable printing Cd-MOF- 1 @PDMS film. The printing process is shown in Figure a. The template is covered on the film to control the incident area of light so as to realize the printing of the target pattern.…”
Section: Resultsmentioning
confidence: 99%
“…1–5 The structures and structure-related properties of MOFs can be tuned by judicious design of both constituents at the molecular level. 6 Owing to their unlimited structural diversity and functional tunability, 7,8 MOFs have become one of the most fascinating classes of materials in numerous areas including gas storage and separation, 9–11 ion exchange, 12 chemical sensing, 13–15 catalysis, 16–18 energy harvesting, 19,20 and biomedicine. 21,22 Since multivariate MOFs were reported by the Yaghi group, and more and more multi-component MOFs with complementary or contradictory properties were created to obtain better performance, 23–25 tremendous efforts have been devoted to introducing multiple metal centers or ligands to improve the properties of the targeted MOF materials.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among MOFs, titanium-based metal–organic frameworks (Ti-MOFs) have garnered special attention due to their excellent photocatalytic activity. 9–21 Nevertheless, the scarcity of Ti-MOFs has limited the research in this area, with the focus mainly on two Ti-MOFs (MIL-125 and MIL-125-NH 2 ) reported over ten years ago. 22–24 Therefore, there is an urgent need to synthesize new Ti-MOFs.…”
Section: Introductionmentioning
confidence: 99%